The impact of alternative packaging on the life cycle of wine on tap - Stefano Massaglia; Tibor Verduna; Vincenzo Varchetta; Filippo Brun; Simone Blanc (Wine Economics and Policy, 2023)
Sustainability is a key objective of development policies within international organizations, and it is also progressively gaining importance in the wine industry as a whole and, more specifically, in the draught wine market. The competitive conditions of the wine sector and the evolution of consumption styles have led to an increasing need for more accurate management strategies and analysis activities to determine the performance of wineries. This study aims to analyse both the environmental and the economic concerns of a commercial development strategy implemented by an Italian winery that uses three packaging formats (glass bottle, one-way PET keg, and reusable steel keg) in the sale of Falanghina PGI wine on three different markets (domestic, Italy; regional, Germany; and international, USA). By assessing the environmental and economic impact of the different formats on the three scenarios through LCA and LCC analysis, it is revealed that the economic and environmental sustainability of packaging types can vary significantly depending on the market destinations. In any case, the results show that PET, and especially reusable materials such as steel, can lead to a marked reduction in impacts on the market for tapped wine.
Keywords: 330; Life Cycle Assessment (LCA); Life Cycle Costing (LCC); Wine; Packaging; Sustainability